Bilateral Borderline Serous Ovarian Tumor Following Three Cycles of Clomiphene Treatment in 19 Years Old Subfertile Woman with Polycystic Ovaries: A Case Report - Gelişen, Orhan; Koçak, Müberra; Köse, Faruk; Boran, Nurettin; Demir, Berfu; Özfuttu, Ahmet (Gynecology Obstetrics & Reproductive Medicine, 2006)
Clomiphene Citrate (CC) is one of the most comprehensively registered agent for ovulation induction in women with polycystic ovarian syndrome (PCOS). CC is regarded as safe and cost effective agent with very f ew complications. During the last 20 years, the potential association between the use of ovulation induction agents and the risk of ovarian neoplasm has become a topic of considerable scientific and public health interest. We report a woman who developed bilateral serous borderline ovarian tumor following three cycles of CC f rom normal appearing ovaries. The condition was diagnosed using baseline ultrasound of the aftercoming CC cycle and immediate diagnostic laparoscopy followed by a converting laparotomy for an accurate staging was performed. We also review published case reports of borderline ovarian tumors following ovulation induction to update the medical literature about this rare yet serious condition may be encountered by physicians providing infertility treatment. A borderline ovarian neoplasm in polycystic ovaries should be considered if a patient develops unforeseen ovarian mass (es) following ovulation induction.